Geowizualizacja wpływu czasów wschodu i zachodu Słońca na godziny dyżurowania Lotniczego Pogotowia Ratunkowego - Wielebski, Łukasz (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2017)
The varying length of daytime (the period of time between sunrise and sunset) influenced by seasons and geographic location, also affects the on-call time of some aeromedical emergency service teams stationed at Polish Medical Air Rescue (PMAR) bases in Poland. The article presents geovisualizations of data from 2017 which illustrate the impact of sunrise and sunset times on the on-call time of PMAR bases and the level of protection of Polish territory for airborne medical aid.
Keywords: geovisualization; sunrise; sunset; Helicopter Emergency Medical Service (HEMS); Polish Medical Air Rescue (PMAR)